“FEATURES OF COLLOQUIAL SPEECH IN MODERN RUSSIAN” (Bulletin of Innovative Research, 2026)
The article examines the main features of colloquial speech in the modern Russian language. The study analyzes such characteristics as spontaneity, situational dependence, the use of incomplete sentences, frequent use of particles, syntactic simplicity, and emotional expressiveness. Based on scientific sources, quotations and examples are provided to illustrate the functioning of colloquial speech in everyday communication.